Novel blood product transfusion regimen to prevent clotting and citrate accumulation during continuous renal replacement therapy with regional citrate anticoagulation in children - Sun, Yuelin; Li, Dong; Bai, Ke; Xu, Feng; Liu, Chengjun; Dang, Hongxing (Frontiers in Pediatrics, 2023)
OBJECTIVE: Introduce a novel protocol to prevent clotting and citrate accumulation (CA) from blood product transfusion (BPT) during continuous renal replacement therapy (CRRT) with regional citrate anticoagulation (RCA). STUDY DESIGN: We evaluated clotting and CA-related complications in children receiving RCA-CRRT with different BPT protocols. RESULTS: Twenty-six children received 44 partial replacement of citrate transfusion protocols (PRCTPs) and 15 children received 20 direct transfusion protocols (DTPs). The two groups had similar in vitro ionized calcium (iCa) concentrations (PRCTP: 0.33±0.05mmol/L, DTP: 0.31±0.06mmol/L), total filter lifespan (PRCTP: 57.53±16.74, DTP: 50.65±16.62 h), and filter lifespan after BPT (PRCTP: 27.85±13.31, DTP: 23.39±13.78 h). The two groups had no significant differences in arterial pressure, venous pressure, and transmembrane pressure before, during, or after BPT. Neither treatment led to significant decreases in WBC, RBC, or hemoglobin. The platelet transfusion group and the FFP group each had no significant decrease in platelets, and no significant increases in PT, APTT, and D-dimer. The most clinically significant changes were in the DTP group, in which the ratio of total calcium to ionized calcium (T/iCa) increased from 2.06±0.26 to 2.52±0.46, the percentage of patients with T/iCa above 2.5 increased from 5.0% to 45%, and the level of in vivo iCa increased from 1.02±0.11 to 1.06±0.09 mmol/L (all P<0.05). Changes in these three indicators were not significant in the PRCTP group. CONCLUSIONS: Neither protocol was associated with filter clotting during RCA-CRRT. However, PRCTP was superior to DTP because it did not increase the risk of CA and hypocalcemia.